Concept of complications of reproductive aging in women for anti-aging therapy. Literature review - Z. M. Dubossarska; Y. O. Dubossarska; L. P. Grek; V. V. Radchenko (Publishing House TRILIST, 2020)
Modern mankind, through the development of medicine and using its scientifically grounded innovations has learned to prolong human life. In Ukraine as in the whole world there is a tendency to increase in life expectancy. Since aging is a natural physiological process, a person from time immemorial has been preoccupied with the search for the so-called "Philosophy Stone" is a substance that prevents aging. This article analyzes data from scientific publications on modern aspects of the problems associated with aging of the female body. It has been proven that aging and anti-aging processes substantiate the individualization of modern approaches to the correction of pre- and perimenopause complications. The general strategy for maintaining of women's health in peri- and postmenopause according to the International Menopause Society includes menopausal hormone therapy, taking into accounts the therapy goals and individual risk factors. Despite all the desire to give a modern definition of aging, it is currently not possible, therefore in this literature review an attempt is made to analyze the known strategies of premature aging to develop the potential for prolonging active life. In any case, the doctor needs to correlate the benefits and risks of menopausal hormone therapy, taking into account individual risk factors and select appropriate rehabilitation methods aimed at "improving the female face" of the classic image of old age. Since the role of estrogen deficiency in the formation of perimenopausal complications and especially premature aging, is not questioned, anti-aging strategies should be considered a pathogenetically justified method of treating vasomotor, psychosomatic symptoms and sleep disorders, as well as a method of preventing metabolic syndrome. It should be remembered that hormone therapy has a number of limitations and contraindications, which is an incentive for every doctor to contribute to prolongation of the active and healthy life of women 40+ and 50+ years old. Creation of a conceptual model for overcoming the complications of reproductive aging and especially cardiovascular events, osteoporosis, cerebrovascular pathology based on the identification of risk factors will allow to develop the protective anti-aging therapy not only to prolong a woman's life, but also to improve its quality